Long-term response with the atypical reaction to nivolumab in microsatellite stability metastatic colorectal cancer: A case report - Nataliya Babyshkina; Nataliya Popova; Evgeny Grigoryev; Tatyana Dronova; Polina Gervas; Alexey Dobrodeev; Dmitry Kostromitskiy; Victor Goldberg; Sergei Afanasiev; Nadejda Cherdyntseva (Drug Target Insights, 2024)
Immunotherapy has become an integral part of a comprehensive treatment approach to metastatic colorectal cancer (mCRC). Nivolumab (Opdivo) is a human immunoglobulin G4 monoclonal antibody that blocks the interaction between the programmed cell death 1 (PD-1) receptor and its ligands 1/2 (PD-L1/PD-L2), leading to inhibition of T-cell proliferation, cytokine secretion, and enhanced immune response. The US Food and Drug Administration (FDA) has approved this drug for use in high microsatellite instability (MSI-high)/deficiencies in mismatch repair (dMMR) advanced CRC patients. However, its efficacy is extremely limited in microsatellite stability (MSS)/mismatch repair proficient (pMMR) patients. We report a case of a 42-year-old man diagnosed with MSS/pMMR mCRC who has achieved a durable response to nivolumab after a progression under chemotherapy with antiangiogenic treatment. We observed for the first time an atypical response after 8 months of nivolumab treatment, with the regression of previous primary pulmonary lesions and the presence of new para-aortic lymph node lesions. This report demonstrates that a subset of pretreated mCRC patients with the MSS/pMMR phenotype may benefit from nivolumab and these patients need more attention.